Extending noninterference properties to the timed world - Huang, J; Roscoe, A (2006)
Most previous work on information flow in process algebras has been based on untimed models of concurrency. It is obvious, however, that an observer might well use time to gain information about what a high-level user of the system is doing. We use the priority took view (a discrete timed model) to extend several traditional untimed noninterference properties to the timed world. These are the determinism-based conditions of [14], [15] and [17], and Forster's local noninterference properties [6], [7]. Copyright 2006 ACM.